Freezing time, preparing for the future: The stockpile as a temporal matter of security. (December 2019) - Folkers, Andreas
This article analyses stockpiling as a security device that hoards time, stores power and buffers disruptions. The stockpile is a temporal matter of security by virtue of its ability to freeze time and to prepare for future emergencies. Stockpiling is informed by anticipations of threats but also materially underpins expectations. After unpacking the temporal ontology of stockpiling, the article traces its history as a security device and technology of power. Stockpiling enabled the emergence of the earliest states by establishing the means to store surpluses and centralize power. In modernity, stores became more dispersed as money, commodity exchange and new infrastructures made it possible to procure resources through circulation. In the 20th century, stockpiling became a reflexive security device reactive to risks associated with the disruption of these circulations. Finally, the article illuminates the role of reserves in contemporary German catastrophe preparedness to show that stockpiling remains an important security technique. Yet fiscal austerity and budgetary constraints limit security stockpiling. To compensate for the absence of public security stores, the government is prompting citizens to establish emergency stockpiles. The article offers a theoretical, historical and empirical engagement with stockpiling and thereby further elucidates the material politics of anticipation.